2021
DOI: 10.3390/children8020097
|View full text |Cite
|
Sign up to set email alerts
|

Is Chest Compression Superimposed with Sustained Inflation during Cardiopulmonary Resuscitation an Alternative to 3:1 Compression to Ventilation Ratio in Newborn Infants?

Abstract: Approximately 0.1% for term and 10–15% of preterm infants receive chest compression (CC) in the delivery room, with high incidence of mortality and neurologic impairment. The poor prognosis associated with receiving CC in the delivery room has raised concerns as to whether specifically-tailored cardiopulmonary resuscitation methods are needed. The current neonatal resuscitation guidelines recommend a 3:1 compression:ventilation ratio; however, the most effective approach to deliver chest compression is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…SI is delivered over 20 s, followed by a ‘pause’ of 1 s when pressure is back to a positive end expiratory pressure (PEEP) of 5–8 cm H 2 O. Heart rate assessment is performed every 45–60 s, and CC+SI is continued until ROSC 22–24. Chandra et al demonstrated that high positive pressure during CC increases intrathoracic pressures and concurrently increased carotid blood flow (18.7 (4.7) vs 5.1 (1.1) mL/min, p<0.05) 11 12.…”
Section: Chest Compression With Sustained Inflations (Cc+si)mentioning
confidence: 99%
“…SI is delivered over 20 s, followed by a ‘pause’ of 1 s when pressure is back to a positive end expiratory pressure (PEEP) of 5–8 cm H 2 O. Heart rate assessment is performed every 45–60 s, and CC+SI is continued until ROSC 22–24. Chandra et al demonstrated that high positive pressure during CC increases intrathoracic pressures and concurrently increased carotid blood flow (18.7 (4.7) vs 5.1 (1.1) mL/min, p<0.05) 11 12.…”
Section: Chest Compression With Sustained Inflations (Cc+si)mentioning
confidence: 99%
“…While the current neonatal resuscitation guidelines recommend a 3:1 compression to ventilation ratio, it was recently demonstrated that providing continuous chest compressions superimposed with high distending pressure or sustained inflation may reduce the time to return of spontaneous circulation and mortality in both asphyxiated piglets and newborn infants. A review by Kim et al [ 7 ] summarizes the currently available evidence of continuous chest compressions superimposed with sustained inflation.…”
Section: Cardio-circulatory Supportmentioning
confidence: 99%
“…Last year, several articles on different aspects related to neonatal resuscitation were published in the journal Children. The topics covered included staff training [ 1 , 2 ], technological aspects [ 3 , 4 , 5 , 6 ], and the investigation of “new” clinical interventions [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
mentioning
confidence: 99%
“…Finally, two interesting articles have added information and offered hypotheses on patient management during the advanced phase of neonatal resuscitation. Kim et al extensively reviewed the existing experimental and clinical evidence on chest compressions along with sustained inflation during cardiopulmonary resuscitation in neonates [ 11 ]. The findings suggest that this new approach is likely to be more effective than the currently used 3:1 compression to ventilation ratio in terms of a shorter time to the return of spontaneous circulation (ROSC), decreased mortality, and improvement in other respiratory and hemodynamic parameters.…”
mentioning
confidence: 99%